A Zn(II) luminescent complex with a Schiff base ligand: solution, computational and solid state studies. Issue 6 (19th March 2018) - Martínez, Sebastián; Igoa, Fernando; Carrera, Ignacio; Seoane, Gustavo; Veiga, Nicolás; De Camargo, Andrea S. S.; Kremer, Carlos; Torres, Julia
Abstract: A new mononuclear complex of zinc(II), [Zn(HL)2 ]∙2DMF (H2 L = ( E )- N′ -(( E )-(hydroxyimino)butan-2-ylidene)salicyloylhydrazide, DMF =  N, N -dimethylformamide), was prepared and characterized. Single-crystal X-ray crystallography revealed a six-coordinate zinc(II) surrounded by nitrogen of the oxime function and oxygen and distal nitrogens of the acylhydrazone group. This entity also exists in solution as demonstrated by 1 H-NMR and potentiometric titrations. The computational analysis showed that the molecular orbitals involved in the main electronic transitions of the complex species in solution are centered on the ligand with negligible contribution of the metal ion. The photophysical properties of the complex were evaluated in solution and in the solid state. Luminescence studies showed that the solid has a strong emission at 550 nm with a large Stokes shift with respect to absorption. The solid state fluorescence emission is ascribed to ligand-centered and/or ligand-to-ligand charge transfer transitions, following the DFT results in solution. A comparison with a previously reported mononuclear [Zn(HL)2 ] allowed the investigation of the influence of DMF molecules in the structural packing and the luminescence properties. Abstract :